Feasibility of Radial Endobronchial Ultrasound-Guided Bronchoscopic Cryobiopsy without Fluoroscopy for Lung Parenchymal Lesions. (15th November 2017) - Chang, Chih-Hao; Lee, Chung-Shu; Li, Shih-Hong; Chung, Fu-Tsai; Wang, Chih-Wei; Juan, Yu-Hsiang; Hu, Han-Chung; Li, Li-Fu; Chen, Ning-Hung; Yang, Cheng-Ta; Kao, Kuo-Chin
Abstract : Background . Cryobiopsy is used to biopsy peripheral lung lesions through flexible bronchoscopy with fluoroscopic guidance. However, fluoroscopy is not available at some institutions. This study evaluated the feasibility of radial endobronchial ultrasound-guided bronchoscopic cryobiopsy without fluoroscopy. Methods . This retrospective study was conducted at Chang Gung Memorial Hospital, Linkou branch, in Taiwan. This study enrolled patients who received bronchoscopy examinations with cryotechnology between July 2014 and June 2016. The data were collected through medical chart review. Results . During the study period, 101 patients underwent bronchoscopy examinations with cryotechnology. Ninety patients with endobronchial tumors were excluded from this study. Eleven patients who underwent radial endobronchial ultrasound-guided bronchoscopic cryobiopsy for lung parenchymal lesions were enrolled into this study. The mean age was 61.1 ± 13.8 years. Five patients were men, and the other six were women. The number of cryobiopsies ranged from 1 to 3. In the histological biopsies, the mean specimen diameter was 0.53 ± 0.23 cm, and the mean biopsy area was 0.20 ± 0.19 cm 2 . Nine of 11 patients had pathological diagnoses. No complications, including pneumothorax, respiratory failure, or major bleeding, were recorded after the procedure. Conclusions . Endobronchial ultrasound is used to ensure biopsy location, and endobronchial ultrasound-guided cryobiopsy is a feasible technique to biopsy peripheral lung lesions in selected cases at institutions without fluoroscopy equipment. This study provided some rationale for further studies examining the impact of fluoroscopy.